Cultural Feminism Found in the Asne Seierstad’s Kabul - Alief, Vicky Radian; Farijanti, Dian (Universitas Swadaya Gunung Jati, 2015)
The result of this study may add to the research literature refrences and add insight to the reader about the image women with the feminism literature review.This research is expected to give contribution to this language teaching using novel as the authentic media, particularly in teaching reading. Novel is narrative text informing of prose with a long shape that including some figures and fiction event. In this case, the study attempted to analyze text about Cultural feminism tht contains in the novel. The text analyzed is a novel entitled The Bookseller of Kabul written by Asne Seierstad, a Norway journalist who spent four months to write the novel after reporting civil war in Afghanistan. This novel mostly describes the portrayal of women in the context of gender relation in Afghanistan after the fall of Taliban, around 2001s.